Marine Circular Economy towards Post-Disaster Reconstruction for Sustainability: Experiences in a Small Coastal Town of Northeast Japan - Yuta Uchiyama, Ai Tashiro1; Kohsaka, Ryo (European Journal of Sustainable Development, 2018)
The wealth of evidence on the conservation effects of development and utilization of ocean, whereas what shapes behavioral change remains unknown, particularly of fishermen. Few previous studies incorporate measuring changes in fishermen’s behavior. This study aims to investigate what changed behavior and perception of fishermen toward marine circular economy in Japan. We selected a unique case of marine-linked practical change of fishermen’s behavior. Our study area, Minamisanriku town in Miyagi Prefecture, was affected in the 2011 earthquake and tsunami. The town incorporated marine circular economy (MCE) into post-disaster reconstruction project: Fishermen reduced farming facilities to one-third of that before the disaster and the quality of oyster improved. To indicate the determinant facts of the practical change, we used ordered probit model for fishermen recognition on the effectiveness of integrating marine conservation into post-disaster reconstruction. Our main finding was different recognition level existed amongst fishermen. It was associated with branch affiliation and hope level for the sustainable fishing culture by the next generation. This study provides understanding a tangible and measurable change in recognition can be bridge the gap between idea and practice. This study suggests horizontal collaboration among between branches would lead to marine conservation attitude through community-based post-disaster reconstruction. Keywords: Marine circular economy, fishermen’s recognition, post-disaster reconstruction, Japan